Entrepreneurship in family firms: an updated bibliometric overview - Muhammad Anwar; Thomas Clauss; Natanya Meyer (Review of Managerial Science, 2023)
Research on entrepreneurship in family firms has grown exponentially over the past two decades. Due to the various theoretical perspectives and contexts found here however, this body of research remains fragmented, with a unified understanding of the current state of knowledge and the opportunities for future research in the field continuing to lack. In this study, we address this gap by conducting an updated bibliometric analysis of the research on entrepreneurship in family firms. Here we integrate two different bibliometric methods to provide a more comprehensive picture of the field, unveiling its intellectual foundations and current research discourses and how these two are related. To do this, we first conduct a co-citation analysis clustering the intellectual foundations of the research on entrepreneurship in family firms. Second, a bibliographic coupling of recent publications from 2010 to 2021 provides a transparent structure of current research discourses. Third, analyzing which intellectual foundations are primarily cited in each current research stream unveils the dominant theoretical paradigms in the current state of research. Analyzing 570 published studies, we identified four intellectual foundations of entrepreneurship in family firms: socioemotional wealth (SEW), entrepreneurial orientation, family-embedded resources, and agency theory. The current research can be clustered into seven main discourses: entrepreneurial motivation, gender and success, entrepreneurial orientation, individual and firm-level characteristics, the family embedded network, family firm internationalization, and family heterogeneity. An integrative network diagram provides an overview of the research field's development while also identifying the gaps to be addressed by future research.
Keywords: L26; L25; Z11; 650; Bibliometric coupling; Bibliographic coupling; Co-citation analysis; Corporate entrepreneurship; Entrepreneurial orientation; Entrepreneurship; Family business; Family firm